The clinical severity of hemoglobin S/Black (Aγδβ)0‐thalassemia. Issue 11 (28th April 2017) - Cancio, Maria I.; Aygun, Banu; Chui, David H. K.; Rothman, Jennifer A.; Scott, J. Paul; Estepp, Jeremie H.; Hankins, Jane S.
Abstract: Hemoglobin S/Black ( A γδβ) 0 ‐thalassemia is a rare sickle cell disease (SCD) variant. On the basis of limited descriptions in the literature, the disease is reported as a mild microcytic anemia with an uncomplicated course. We report the clinical and laboratory data of nine patients whose diagnoses were confirmed by DNA‐based techniques. Despite having mild anemia and high fetal hemoglobin level postinfancy, these patients developed many of the classic complications of SCD, including vaso‐occlusive crisis, acute chest syndrome, avascular necrosis, and cholelithiasis. On the basis of these findings, we recommend that patients with this rare disorder receive specialized hematology care according to SCD guidelines.